Analisis Perbandingan Metode SAW, WP dan TOPSIS Pada Sistem Pendukung Keputusan Pemilihan Wedding Organizer di Jakarta - Ahmad Syahroni; Farah Cahyana Ramadhani; Muhamad Dio Oktafani; Muhammad Rifky Adrian Ardani; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Currently, there are various wedding organizer (WO) services available that make it easier for the bride and groom to prepare for their wedding. Each WO service provides a large selection of attractive, competitive and specific wedding service packages. On the other hand, this sometimes makes it difficult for the bride and groom to choose a WO. To assist in the selection of decision making, a Decision Support System (DSS) approach is used. The criteria used include: make-up, package prices, concepts, documentation, and services. This study aims to analyze what will happen from the Simple Additive Weighting (SAW), Weighted Product (WP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods so that they can influence which method is more relevant to apply. in the case of the WO election in Jakarta. Although in general the three methods are relatively equally relevant, in certain special conditions the SAW method is considered relevant enough to be implemented in this case compared to the WP and TOPSIS methods.